Stereochemical configuration and selective excitation of the chiral molecule halothane. (11th November 2016) - Pitzer, Martin; Kastirke, Gregor; Burzynski, Phillip; Weller, Miriam; Metz, Daniel; Neff, Jonathan; Waitz, Markus; Trinter, Florian; Schmidt, Lothar Ph H; Williams, Joshua B; Jahnke, Till; Schmidt-Böcking, Horst; et al.
Abstract: X-ray single-photon ionization and fragmentation of the chiral molecule halothane from a racemic mixture have been investigated using the cold target recoil ion momentum spectroscopy technique. Two important facets related to the core ionization of this species are examined: Firstly, the distinction of enantiomers (mirror isomers) and the determination of absolute configuration on a single-molecule level by four-body Coulomb explosion; secondly, the interplay of site-selective excitation and fragmentation patterns. These results are easily transferable to other molecular species and show the wealth of features that can be investigated by coincidence spectroscopy of chiral molecules.